The variation of acquisition, consolidation memory and coordination pattern of elbow joint in short service badminton before and after aerobic training - Darzabi, T.; Taheri, H. R.; Kakhki, A. R. S. (Annals of Applied Sport Science, 2018)
Background. Consider the fact that the implementation of aerobic exercise can be effective in the learning and acquisition process, and that training athletes to acquire new skills is appropriately done in terms of the primacy and recency of the training time for aerobic activities such as the warm-up. Objectives. The purpose of the present study was to investigate the effect of moderate-intensity aerobic activity before training on the acquisition, consolidation memory, and coordination pattern of the elbow joint with regard to the short service in badminton. Methods. Thirty-eight participants aged 17 to 19 years were selected by convenience sampling and purposive sampling. The participants were randomly assigned to two experimental groups (n =14 and n = 10) and a control group (n = 14) based on aerobic capacity. Before and after the badminton short service training, the participants ran for 20 minutes on a treadmill at a speed of about 70% of their maximum heart rate. At various stages of training, the precision of the shuttlecock landing spots was measured based on the French test at the time of acquisition, immediate retention, retention, and transfer in all three groups. Also, using motion analysis, the range of motion of the wrist, elbow, and shoulder joints was measured. Moreover, by using a PCA, the coordination pattern of the range of motion of the elbow joint was compared in all three groups. Results. There was no significant difference between the groups in terms of the accuracy of the short service in badminton in the French test based on aerobic exercise before and after training (p<0.05).A significant difference was observed between all parts of the test and the transfer test (p>0.05). Also, there was no significant difference in the coordination pattern of the range of the elbow joints between the groups. Furthermore, the repeat of service has no significant effect on the motion pattern in any way. Conclusion. According to the impact of moderate-intensity aerobic activity before and after training on the acquisition, consolidation of memory, and coordination pattern of the elbow joint, there was no significant difference in the accuracy of the short service in badminton.